Provision of Laboratory services [Tender documents : T31383956] (MENA Report, 2016)
Pite municipality~s purchasing department has been instructed to procure the overall need for lab services for the following municipalities with its companies: Arjeplog Municipality, Arvidsjaur Municipality, Boden Municipality, the Municipality of Gllivare, Haparanda, Jokkmokk municipality, Kalix, Kiruna, Lule, Pajala Municipality , Pite, lvsbyn municipality, the municipality of verkalix and vertorne.